J = S+5
(J-3) = 2(S-3)
Putting the first value for J into the second equation:
S+5 - 3 = 2S - 6
Simplifying:
S+2 = 2S - 6
S = 8
So, Steve is 8, and Jack = S+5 = 13
Hope that helps! ;-)
2007-01-25 03:30:54
·
answer #1
·
answered by MamaMia © 7
·
2⤊
1⤋
J = S+5. J-3 = 2(S-3). Therefore S+2 = 2S - 6. Add 6-S to each side: 8 = S. Steve is 8 years old and Jack is 13. Three years ago, they were 5 and 10.
Another way to look at is is that Jack has always been five years older than Steve, but three years ago he was also twice Steve's age, so three years ago Steve must have been five. Then solve it from there.
2007-01-25 11:35:23
·
answer #2
·
answered by Amy F 5
·
0⤊
1⤋
Jack is 13 and Steve is 8
2007-01-25 11:44:07
·
answer #3
·
answered by Emma Michele 2
·
0⤊
0⤋
Steve's Age=x
Jack's age=x+5
Before 3 years
Steve's age=x-3
Jack's age=(x+5)-3 => x+2
Jack=twice of steve
x+2=2(x-3)
x+2=2x-6
x=8
So, steve=8
Jack=x+5 => 8+5=13.
Jack=13, Steve=8
2007-01-25 12:08:25
·
answer #4
·
answered by Rajesh 2
·
0⤊
0⤋
In all these kinds of problems, you first need to assign a variable to the values you are trying to find out. In this case you are trying to find out how old these guys are now, so:
j=jack's age now
s=steve's age now
Now you just use those varibles to write algebra sentences (equations) that match the english sentences in the problem
Jack is 5 years older than steve: j=s+5
Three years ago, jack was twice as old as steve: (j-3)=2*(s-3)
reducing:
(j-3)=2*(s-3)
j-3=2s-6
j=2s-3
Now we have the two equations and two unknowns and can solve.
j=s+5
j=2s-3
We can solve this several ways. The easiest is probably substitution. We replace the "j" in the first equation with what "j" is equal to in the second equation.
(2s-3)=s+5
and we solve
2s-3=s+5
2s=s+8
s=8
remembering that j=s+5
j=8+5=13
j=13
jack 13, steve 8
Jack is 5 years older than Steve now, and three years ago Jack was 10 and Steve was 5, so Jack was twice as old then.
voila
keep at it
math is power
2007-01-25 11:38:52
·
answer #5
·
answered by enginerd 6
·
0⤊
1⤋
Jack is 13 and Steve is 8.
2007-01-25 11:36:37
·
answer #6
·
answered by abigail_evelyn 2
·
0⤊
1⤋
Jack is 5 years older than Steve.
j = s + 5
Three years ago, Jack was twice as old as Steve.
(j - 3) = 2(s - 3)
So, substituting s+5 for j, we get
s+2 = 2s-6
s = 8
Steve is 8, Jack is 13.
2007-01-25 11:34:30
·
answer #7
·
answered by Andrew D 1
·
0⤊
1⤋
Jack is 13
Steve is 8
J = S+5. J-3 = 2(S-3). Therefore S+2 = 2S - 6. Add 6-S to each side: 8 = S
2007-01-25 11:37:58
·
answer #8
·
answered by ĦΛЏĢħŦŞŧμρђ 2
·
0⤊
0⤋
Jack is 7 and Steve is 5.
2007-01-25 11:32:59
·
answer #9
·
answered by herzoo64 2
·
0⤊
2⤋
dont I need at least one of their ages to answer this
2007-01-25 11:33:52
·
answer #10
·
answered by bm 2
·
0⤊
3⤋